Preconditions for a lenient type of punishment on parole international experience (Journal of actual problems of jurisprudence, 2022)
The article describes the international experience of the type of punishment and restraint for the early release of prisoners. The experience of various world powers is considered. Who practice early release, commutation of sentences in general. International experience with criminal early release shows different practices. Let's consider some of them, and how it is applied or sees its reflection in Kazakhstani practice. They also talk about the prospect of parole, which is the most effective incentive for a convict to positive behavior in places of detention, since it is impossible to achieve correction without encouraging measures. Every convicted person, after sentencing and arriving at the place of serving the sentence, knows when he must be released from places of imprisonment after the expiration of the sentence. At the same time, he knows not only the year, month and day, but even the hours of such release, which is directly provided for by law. Knows the procedure for parole, which allows you to be released much earlier than the end of the sentence established by the court, subject to proper behavior.Keywords: criminal early release, code, criminal code, international experience, mitigation.